熱音響理論を用いた積層金網再生器の エネルギー変換効率の数値計算 - 上田, 祐樹; FARIKHAH, Irna (Teion kōgaku, 2016)
A simple numerical method to calculate the performance of a stacked-screen regenerator is proposed. The method is based on a well-known thermoacoustic theory but uses some empirical factors that were determined by the measurement of viscous losses in stacked-screen regenerators. The efficiency of the energy conversion in a stacked-screen regenerator is calculated using the method and compared with the experimental results. Furthermore,a comparison of the numerically calculated efficiencies in stack-screen and tube-array regenerators is performed.